THE EFFECT OF FINANCIAL SUSTAINABILITY ON BANKING STABILITY (World Bulletin of Social Sciences, 2022)
The research aims to explore the impact of financial sustainability as an independent variable on banking stability as a dependent variable, in a sample of Iraqi banks. Commercial banks (16 banks) were listed in the Iraqi Securities Commission during the extended period (2006-2020), and the relationship between the variables was tested and analyzed, both statistically and quantitatively, according to the method of analyzing time data (panel data) and ready-made statistical programs (Eviews12) were used. Test hypotheses on the basis of their results after intellectual inference from the results of analysis, measurement and hypothesis testing, which proved the impact of financial sustainability on banking stability, based on the regression model.